Iraq : 2017 Article IV Consultation and Second Review under the Three-Year Stand-by Arrangement-and Requests for Waivers of Nonobservance and Applicability of Performance Criteria, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report ;, 2017)
Iraq is an oil-dependent and state-dominated fragile economy that has been hit hard by the conflict with ISIS and the fall in oil prices. The conflict has hurt the economy through displacement and impoverishment of millions of people, and destruction of infrastructure and assets. The oil price decline has resulted in a massive reduction in budget revenue, pushing the fiscal deficit to an unsustainable level. The authorities are responding to the crisis with ambitious but necessary fiscal adjustment while maintaining their commitment to the exchange rate peg, which provides a key nominal anchor in a highly uncertain environment.